Attempts at redress through the lens of social identity: housing, land and property of the displaced in Cyprus - Waardt, Mijke de (International journal of transitional justice, 2021)
Transitional justice measures, particularly reparations, have started to address housing, land and property (HLP) issues in relation to internally displaced persons (IDPs), but HLP grievances have not decreased. Because it is difficult to meaningfully engage IDPs in reparations and redress, contextualized approaches are suggested for remedies to become effective. We propose a lens of social identity theory (SIT) to illuminate the potential for HLP attempts for redress to be expanded to groups in intractable conflict. Based on research in Cyprus, we argue that SIT enables the scrutiny of whether and how legal decisions and administrative remedy mechanisms meaningfully relate to IDPs’ notions of victimhood and (in)justice. We show that attempts for redress may act to maintain competitive narratives and exclusionary social identities in Cyprus. An inclusive victimhood narrative may shift categories available for an intergroup social identity for Cypriots, making it more likely for actual progress on the HLP issue.